The impact of living with long‐term conditions in young adulthood on mental health and identity: What can help?. (25th July 2019) - Wilson, Ceri; Stock, Jennifer
Abstract: Background: It has been suggested that the mental health impacts of living with long‐term conditions are greater in young adulthood compared to older adulthood, due to greater disruption to identity and routine life events. Objectives: To explore the impact of living with long‐term conditions in young adulthood on mental health and identity, and what helps living well with these conditions. Methods: Fifteen in‐depth interviews with young adults with various conditions were conducted and analysed thematically. Results: Themes related to the impacts on mental health and identity include the following: negative mood and depression; anxiety and fear for the future; and identity as 'ill'/abnormal compared to former self and 'normal' others. Themes related to suggestions for addressing negative impacts include the following: promotion of positive thinking; support reaching acceptance with altered identity and limitations (through stages of denial, anger, depression, then acceptance); and more professional mental health support. Discussion: In order to promote mental health and a positive sense of self/identity, young adults with long‐term conditions should be offered advice and support on positive thinking; the long and difficult process of reconstructing identity; and reaching acceptance. This is particularly important for young adults for whom the identity reconstruction process is more complex and psychologically damaging than for older adults, as this life stage is associated with health/vitality and illness represents a shift from a perceived normal trajectory to one that appears and feels abnormal.